La « minorité » en tant que force politique dans le système politique occidental - Contogeorgis, Georges (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
In this paper the author questions the future of minorities as a political force. He notes in this respect that religion no longer plays a preponderant role in occidental societies as a mobilizing force for autonomous action. Religious minorities no longer succeed in intervening in politics. The author underscores the contrast with the prevailing situation in Eastern socialist societies where the Church is the only institution that can stand up to the State which tends to monopolize politics. He also raises the problems caused by the coexistence of religious and linguistic or ethnic groups.